Rapid premixing fuel-water injector in burner combustion - Suardi, Mirnah (2016)
The alternative fuel is attract good attention from worldwide especially for renewable and prevention energy such as biodiesel. Biodiesel is one of the hydrocarbon fuels and it has potential for external combustion. This research used biodiesel Crude Palm Oil (CPO) as fuels in which have been blend with diesel. Biodiesel Crude Palm Oil base (CPO) is free from sulfur and produced by esterification and trans-esterification reaction of vegetable oil with low molecular weight alcohol, such as ethanol or methanol. Rapid mixing injector uses for external combustion especially open burner system. Therefore, the objectives of this research are to investigate the effects of mixture formation between biodiesel and water on using rapid mixing injector and to analyze the influence of mixture formation on flame propagation and combustion characteristics together with the effect of water content on the gas emissions are analyzed. The disadvantages of CPO are high toxic emissions such as NOX and CO while it can cause the reduction on performance of burner system. However, high toxic emission can be solved by using a new concept injector with fuel-water-air premixing. The additional water in combustion process can be reduced the NOX emissions. The results of this research focuses on the mixture formation of spray, flame and exhaust gas emissions. CPO biodiesel has longer spray length and bigger spray area than diesel, but the spray angle is smaller than diesel. Based on flame image, it shows that the flame color between pure fuels and fuel-water mix fuel is totally difference compare to each other. Water mix with fuel has the brightness color and shorter flame than fuels. The exhausts gaseous tested are CO, CO2, HC and NOX. In this research, water premix of percentage up to 15vol% and blending biodiesel ratio was varied from 5vol% - 15vol%. The result shows that increasing of water content will affected decrement of CO, CO2 and HC emissions but increasing the NOX emissions.